The magic rings - Harrison, Paula; Tancredi, Sharon (London nosy crow c 2018, 2018)
A beautiful foal has mysteriously disappeared from the palace stables. The girls have a plan of action, but Lottie is worried. What if they're not brave enough? Or can't keep a secret? After all, it takes more than a few ninja moves to make a proper Rescue Princess
English stories
Keywords: English fictions